Influence of biochar applied to soil on yield and quality attributes of fodder oats - Concilco Alberto, Ernesto; Moreno Reséndez, Alejandro; García Carrillo, Mario; Quiroga Garza, Héctor Mario; Ángel García, Oscar (REVISTA TERRA LATINOAMERICANA, 2018)
Soil is an essential resource for agricultural production. It requires appropriate conditions to promote good crop nutrition and to generate higher yields. Biochar has been widely proposed to improve soil quality and crop productivity. The aim of this study was to evaluate the effects of biochar on yield and quality of fodder oats, in the period from autumn-winter 2016-2017. A randomized block design with four replications was used. Three treatments and one control were employed: T0 = control; T1 = conventional fertilization (120-60-00 kg ha-1); T2 = 2.25 Mg ha‑1 of biochar + conventional fertilization; T3 = 4 Mg ha-1 of biochar + conventional fertilization. The experiment was conducted under f ield conditions using a sowing density of 120 kg ha-1. The evaluated variables were plant height (PH), green matter (GM), dry matter (DM); neutral detergent f iber (NDF), acid detergent f iber (ADF), crude protein (CP), total digestive nutrients (TDN) and dry matter digestibility (DMD). The recorded data were subjected to analysis of variance and the means were compared with the Tukey test (P < 0.05). Signif icant statistical differences (≤ 0.05) were observed for PH and GM, for which T2 had 33 and 102% higher values, respectively, compared with the control. It is concluded that the application of biochar has a positive influence on yield attributes of forage oats. However, more detailed studies should be carried out, considering conditions other than those of the present study.